PSS Parameter Optimization Based on Comprehensive Damping Effect Method Aiming at Actual Grid Characteristics in Northern China. (25th January 2020) - Liu, Xiang-Yu; He, Yu-Ling; Li, Xiao-Ming; Lu, Peng; Cheng, Lun; Li, An-Chang
Abstract : In this paper, we proposed the comprehensive damping effect method to optimize the PSS parameters. Different from other studies, the optimization in this paper is based on both the amplitude-frequency and the phase-frequency properties, while other studies mainly focus on the phase-frequency characteristics. The actual grid data in Northern China are employed to verify the optimization effect in the multimachine system. The proposed method is compared with the engineering method, the existing optimization method, and the commercial software. The comparison shows that the PSS parameters obtained by the proposed method in this paper are superior to those obtained by the engineering experience, the phase-frequency optimization method, and the commercial software. In the cases of different phase-frequency range requirements, the wider the phase-frequency range is, the better the damping effect of the obtained parameters will be.